Penerapan Model Problem Based Learning terhadap Hasil Belajar pada Pembelajaran IPAS Siswa Kelas V SD Negeri 16 Pontianak Selatan - Homsih Homsih; Bistari Bistari; Hery Kresnadi (Departement of Mathematics Education, 2024)
The data in this study were obtained from SD Negeri 16 South Pontianak in class V. The study aims to analyze the learning outcomes of students in IPAS learning before and after using PBL and to analyze whether there is a significant difference in the average learning outcomes in IPAS learning before using the PBL model and after using the PBL model V. The instrument in this study was a test. The data collection technique used is measurement technique. The results of the study students were given a pretest and posttest with questions in the form of multiple choice as many as 30 questions. The average value of the learning outcomes of grade V students of SD Negeri 16 South Pontianak before the application of the PBL model was 58.61. The average value of student learning outcomes after the application of the PBL model is 65.55. Based on the t test calculation of the two averages of pre-test and post test learning outcomes, the difference in the average learning outcomes of students, t count is 5.314 and the t table value is obtained (α = 5% and dk = 33, then the t_table value is 2.03). Based on the calculation results obtained the value of t_ (count) (5.314) > t_table (2.03), then the hypothesis is accepted. So it can be concluded that the application of the PBL model has a significant effect on the learning outcomes of class V IPAS SD Negeri 16 South Pontianak. So it can be concluded that the application of the PBL model has a significant effect on the learning outcomes of class V IPAS SD Negeri 16 South Pontianak.